SOAROAD: An Ontology of Architectural Decisions Supporting Assessment of Service Oriented Architectures - Szwed, P.; Skrzyński, P.; Rogus, G.; Werewka, J. (Informatica, 2014)
SOAROAD: An Ontology of Architectural Decisions Supporting Assessment of Service Oriented Architectures